3D Flapping Trajectory of a Micro-Air-Vehicle and its Application to Unsteady Flow Simulation. (5th June 2013) - Yang, Lung-Jieh; Hsiao, Fu-Yuen; Tang, Wen-Tzu; Huang, I-Cheng
A three-dimensional (3D) trajectory detection framework using two high-speed cameras for the flapping flexible wing of a micro-air-vehicle (MAV) is presented. This MAV, which is called the "Golden Snitch", has a successful flight record of 8 minutes. We embed the flexible wingskin with a nine light emitting diode (LED) array as the light enhancing marker and capsulate it with parylene (poly-para-xylylene) as the protection layer. We confirm an oblique figure of eight trajectory of this MAV's wing with time-varying coordinate data. The corresponding aerofoil of the main wings' profiles was subjected to the time-varying coordinate data, yielding a resolution of a 1/70 wing beating cycle of 15Hz flapping. The trajectory information is first demonstrated as the moving boundaries of an unsteady flow simulation around a flapping flexible wing.